DESIGNING A COLLECTION OF MEN'S AND WOMEN'S CLOTHING BASED ON THE COMPOSITION ELEMENTS OF THE FORMATION OF THE AVIATOR STYLE - ЛУЩЕВСЬКА, О. М.; КРАСНЮК, Л. В.; Буханцова, Л. В. (Art and Design, 2023)
The purpose of this research is the art design of an author's collection of men's and women's clothing based on the compositional elements analysis of aviator-style clothing using modern textile processing technologies. Methodology. The main principles of the systematic approach to the art design of the author's clothing collection are used in the work, namely: literary-analytical research, morphological analysis, the method of system-structural analysis, artistic-compositional analysis; also are used modern methods of studying consumer opinions through online surveys. Results. The trends in the development of fashion and the collections of famous designers in the military style were analysed, as a result, the characteristic features of the aviator style in modern clothes were distinguished. An online consumer survey was conducted and made it possible to determine the range and attractiveness degree of characteristic compositional elements of aviator-style clothing. The creating concept of an author's clothing collection in the aviator style was formed. Based on the results of the research, an author's collection of modern men's and women's clothing was developed with modern technologies for processing denim materials and knitwear. The scientific novelty of the obtained lies in the systematization of the compositional elements of aviator-style clothing formation with their subsequent use in the creation process of a modern clothing collection. The practical significance. The main sub-styles of the military style in modern clothes are revealed. The characteristic features of aviator-style clothing are analysed, singled out, and systematized. The art and compositional foundations of designing a collection of men's and women's clothing in aviator style have been developed as a creative source.